Is Mobile Money Changing Rural Africa? Evidence from a Field Experiment - Catia Batista; Pedro C. Vicente (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
Rural areas in sub-Saharan Africa are typically underserved by financial services. We measure the economic impact of introducing mobile money for the first time in rural villages of Mozambique using a randomized control trial. This intervention led to consumption smoothing through increased transfers as a response to both geo-referenced village-level floods and household-level idiosyncratic shocks. Importantly, we find that the availability of mobile money increased migration out of rural areas, where we observe lower agricultural activity and investment. Our work illustrates how financial inclusion can accelerate African urbanization and structural change while improving welfare in rural areas.
Keywords: O12; O15; O16; O33; G20; R23; 330; mobile money; migration; remittances; technology adoption; insurance; consumption smoothing; investment; savings; Mozambique; Africa